The Effects of Divorce and Marital Discord on Adult Children's Psychological Well-being - Amato, Paul R.; Sobolewski, Juliana M. (American Sociological Review, 2001)
Previous research has demonstrated associations between exposure to parental divorce and marital discord while growing up and children's psychological distress in adulthood. Few studies, however, have attempted to explain these associations. Three pathways are evaluated through which family disruption and discord may affect offspring's well-being: children's socioeconomic attainment, children's marital and relationship stability, and the quality of children's relations with parents. Using 17-year longitudinal data from two generations, results show that divorce and marital discord predict lower levels of psychological well-being in adulthood. Parent-child relationships mediate most of the associations between parents’ marital discord and divorce and children's subsequent psychological outcomes. Marital discord appears to erode children's emotional bonds with mothers, whereas both divorce and marital discord appear to erode children's emotional bonds with fathers. The results highlight the continuing importance of parent-child ties for children's well-being in early adulthood.